Y -:5 = 2/3x + 6 because 6 is 2/3 of 9
add 5 to both sides
y - 5 +:5 = 2/3x + 6 + 5
y = 2/3x + 11
the y intersept is 11 or (0 , 11) when x is 0
when x is 3
y = 2/3 (3) + 11 or 2 + 11 = 13
so a 2nd point could be (3 , 13)
Answer:
G
Step-by-step explanation:
Answer:
B) Variable Expense
Step-by-step explanation:
trust me
Let n = 1
then f(1) = 1^1 - 1 + 2 = 2 so it is true for n = 1
for the next number after n ( n+1) we have f(n+1) =
(n+1)^2 - (n+1) + 2
= n^2 + 2n + 1 - n - 1 + 2
= n^2 + n + 2
= n(n+1) + 2
Now n(n+1) must be divisible by 2 because either n is odd and n+1 is even OR n is even and n+1 is odd and odd & even always = an even number.
So the function is divisible by 2 for n+1 We have shown that its true for n = 1 Therefore it must be true for n = 1,2,3,4 ...
True for all positive integers